O fetiche da tecnologia no espaço agrário : o caso dos assentamentos rurais Jacaré Curituba e Edmilson Oliveira em Sergipe - Santos, Fábio Ferreira (2013)
This study examines the use of technology in rural settlements Gator Curituba and Edmilson de Oliveira, located respectively in the cities of San Francisco and the Caninde Carira in the state of Sergipe and their repercussions on the production of space and the reproduction of peasant families. From a reasoned analysis of the contradictions of the process of production and reproduction of space by human actions arising from the inclusion of capital in the field through the introduction of technologies for public policies the state is present implementing policies for rural settlements, which reverberate territorial transformations in the region. It was observed that in the study area, contradictorily, peasant production units resist cultivating various products that meet the basic needs of food. In the study area, are produced various products for the National School Feeding Programme, National Programme of Use and biodiesel production, to processing industries and for family consumption. However, capital appropriates output for playback, as monopolizes the territory of rural settlements appropriating agricultural production units and redefining peasant from production, social relations of production. In turn, farmers are looking for ways of resistance and permanence in the field through diversification of production, planting crops such as vegetables , vegetables and fruits , friendly products market acceptance , which confirms the strength of these subjects in the creation and recreation of peasantry even being subordinated to capital.